2022
DOI: 10.3389/fmicb.2022.901848
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Novel Therapeutic Candidates Against SARS-CoV-2 Infections: An Application of RNA Sequencing Toward mRNA Based Nanotherapeutics

Abstract: Due to fast transmission and various circulating SARS-CoV-2 variants, a significant increase of coronavirus 2019 infection cases with acute respiratory symptoms has prompted worries about the efficiency of current vaccines. The possible evasion from vaccine immunity urged scientists to identify novel therapeutic targets for developing improved vaccines to manage worldwide COVID-19 infections. Our study sequenced pooled peripheral blood mononuclear cells transcriptomes of SARS-CoV-2 patients with moderate and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…The identification of this RL11_human in this analysis, along with its alignment with the variation profile of the antigen antibody group from the antibody testing, suggests relevance to previous reports [18][19][20]. According to the report by Q. Zhu et al [19], they propose the potential to create a conducive cellular environment that significantly facilitates cell replication and promotes a favorable context for virus replication.…”
Section: Results and Discusstionssupporting
confidence: 65%
See 1 more Smart Citation
“…The identification of this RL11_human in this analysis, along with its alignment with the variation profile of the antigen antibody group from the antibody testing, suggests relevance to previous reports [18][19][20]. According to the report by Q. Zhu et al [19], they propose the potential to create a conducive cellular environment that significantly facilitates cell replication and promotes a favorable context for virus replication.…”
Section: Results and Discusstionssupporting
confidence: 65%
“…Investigation into this phenomenon revealed previous reports of a similar significant increase in the expression of this 60S Ribosomal protein after Covid-19 infection. Z. Khalid et al have previously reported that 60S Ribosomal protein L29 (RPL29) was highly expressed across all COVID-19 infection groups [18][19][20]. The screened 60S ribosomal protein L11 (RL11_human) in this analysis is a component of the 60S ribosomal subunit, a central part of the ribosome, with several important functions: Ribosome conformation: RL11_human plays a crucial role in the conformation and maturation of ribosomes.…”
Section: Results and Discusstionsmentioning
confidence: 92%
“…4 I), indicating that they have a positive role in the enhancement of tumor-associated immunity. Some of the upregulated genes such as CXCL13 [ 21 ] and CXCL11 [ 22 ] and KLK5 [ 23 ] have been experimentally verified in prior studies to regulate humoral immune response and support tumor infiltration. Furthermore, KEGG pathway enrichment analysis showed that these DEGs were mainly enriched in cytokine-cytokine receptor interactions and JAK-STAT signaling pathway pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among these 14 genes (Table S2), some of them are reported to be closely related to COVID-19. RNF187 has been shown to be a biomarker in children with COVID-19 [22]; NCR3 is significantly associated with the decreased proportion of CD8+ T and T helper 2 cells in the peripheral circulation in COVID-19 patients [23]; TEX2 can predict the ventilator-free days of patients with COVID-19 [24]; ITPKB is a hub gene shared by Alzheimer's disease and COVID-19 [25]; TUBG1 is involved in the immune interaction of COVID-19 and lymphoma [26]; RPL14 is a significantly upregulated gene in COVID-19 patients [27]. Besides the above genes, other unreported genes in the AGAE score may also have research significance.…”
Section: Discussionmentioning
confidence: 99%